PENGARUH LINGKUNGAN KERJA, EFIKASI DIRI, PELATIHAN PROFESIONAL DAN PENGHARGAAN FINANSIAL TERHADAP MINAT PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK (Studi Pada Mahasiswa Akuntansi Perguruan Tinggi Swasta di Pekanbaru) - Irma, Ade; Andreas, Andreas; Safitri, Devi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study was conducted with the aim of testing and proving teh influence of thework environment, self-efficacy, professional training and financial rewards oninterest in choosing a career as a public accountant. This research is aquantitative reserch where the data used in this study are primary data and datacollection using a questionnaire measured by a Likert scale. The questionnairewas distributed using gform. The population in this study is a private university inPekanbaru. The sampel in this study were Accountanting Study Program studentsof 2021. The number of samples in this study was 170 respondents, the samplingmethod was Purposive Sampling. Data analysis was carried out using multiplelinear regression processed with the help of the SPSS version 30 program. Theresults of this study indicate that self-efficacy, professional training and financialrewards have an effect on career selection as a public accountant. And the workenvironment does not affect the interest in choosing a career as a publicaccountant.Key wods: work environment, self efficacy, professional training, financialrewards, interest, career choice